Analisis Minat Belajar Siswa SMA Kelas XI Pada Materi Garis Singgung Lingkaran Dengan Menggunakan Aplikasi Geogebra - Sagita Nur Ariyanti; Nunung Hamidah; Riska Nurvela; Wahyu Setiawan (Journal on Education, 2019)
This study aims to determine the effect of the application of geogebra in the material tangent circles on student interest in learning. This study uses a qualitative descriptive method that aims to describe the level of student interest in learning using geogebra applications on tangent circles. The results of this study were obtained from the distribution of instruments in the form of questionnaires for student interest in learning which were then processed using a Likert scale and then analyzed. The place of this research was conducted at SMAN I Cikalongwetan. The population used was all students of SMAN 1 Cikalongwetan with the sample being students of class XI A of SMAN 1 Cikalongwetan. Based on the results of the analysis of the data obtained it can be concluded that the level of student interest in learning after learning to use geogebra can be categorized quite well and students look more enthusiastic when learning to use geogebra. The weaknesses of the application of geogebra in learning in schools are: 1) the limitations of tools / android, 2) the time used is longer because they have to introduce the functions contained in every tool in geogebra, 3) not all students like technology